Epstein‐Barr virus‐positive diffuse large B‐cell lymphoma association is not only restricted to elderly patients. Issue 12 (27th May 2014) - Cohen, M.; Narbaitz, M.; Metrebian, F.; De Matteo, E.; Preciado, M. V.; Chabay, P. A.
<x xml:space="preserve">Abstract</x> Diffuse large B‐cell lymphoma (DLBCL), the most common group of malignant lymphomas, account for 30% of adult non‐Hodgkin lymphomas. The 2008 World Health Organization (WHO) classification included a new entity, Epstein‐Barr virus (EBV)+ DLBCL of the elderly, affecting patients aged 50 years or older. However, some reports of younger EBV+ DLBCL cases, without evidence of underlying immunosuppression, can be found. The role of EBV in tumor microenvironment composition in DLBCL is still not well understood. Our aim was to assess EBV presence and latency pattern as well as tumor T‐cell population in an adult DLBCL series of Argentina. The study was conducted on biopsies from 75 DLBCL patients. EBERs expression was performed by in situ hybridization, while EBV gene expression was analyzed using real‐time polymerase chain reaction. LMP1, LMP2A, EBNA2, EBNA3A, CD4, CD8 and Foxp3 expression was assessed by immunohistochemistry. Nine percent of cases showed EBV expression, with similar frequency among patients younger than 50 years and 50 years or older (13% and 8%, respectively). T‐cell subsets were not altered by EBV presence. Latency type II was the most frequently observed, together with lytic gene expression in EBV+ DLBCL, with ≥20% of EBERs+ cells. These findings suggest that EBV+ DLBCL in our series was similar to the previously described in Asia and Latin‐America, displaying latency II or III expression profile and no age‐specific characteristics. Finally, EBV+ DLBCL may be an entity that is not only restricted to patients who are older than 50 years of age, in consequence the age cutoff revision may be a current goal.